An Analysis of Literary Comprehension and Engagement: Innovative Media to Task-Based Learning in Writing Prose Fiction and Lyrical Poetry in the Second Year of SMAN 13 Kabupaten Tangerang - Fabhia Sakhda Tamtia; Nurhaedah Gailea; Rita Handayani (Indo Publishing, 2026)
This study explores the impact of innovative task-based learning (TBL) approaches on literary comprehension and student engagement in the context of prose fiction and lyrical poetry instruction among second-year students at SMAN 13 Kabupaten Tangerang. Recognizing the challenges students face in understanding and appreciating literary texts, this research investigates how task-based learning strategies can enhance critical thinking, interpretative skills, and overall enthusiasm for literature. Utilizing a qualitative method supported by classroom observations, student feedback, and performance assessments, the study identifies key activities and techniques—such as collaborative, creative writing tasks,—that significantly contribute to deeper engagement with literary content. The findings suggest that when students are actively involved in meaningful, goal-oriented tasks, their ability to comprehend and appreciate both prose fiction and lyrical poetry improves noticeably. The study concludes with recommendations for integrating TBL into literature curricula to foster more dynamic, student-centered learning environments.